A Five Year Economic Programme for Uttar Pradesh - Planning Commission (Planning Commission, 1950)
In drawing up a plan it is essential to define its objective and scope. A comprehensive Plan for economic development must necessarily visualise the maximum utilization of the resources to increase production from land and of manufactured goods, in conditions which ensure maximum employment of the available man-power. But while tins ensures the material happiness and contentment of the people, it is only second in importance to the need for the development of the personality and the character of the people. Mere material improvement does not ensure the enjoyment of a fuller and better life.
(Submitted to the Economic Sub-Committee of the A. I. C. C-April 1950) Uttar Pradesh